PRODUCTION OF CARBON-BASED ADSORBENTS FROM WALNUT SHELLS AND THEIR PHYSICOCHEMICAL PROPERTIES - Dilafruz Sagdullaeva; Dilnoza Salihanova; Akmaljon Khakimov; Abduhalil Kurbonaliev (Western European Studies, 2025)
This study presents the production of carbon-based adsorbents from walnut shells through thermal pyrolysis and steam activation. The process was conducted in an oxygen-free environment at temperatures between 300 and 800°C to form a porous carbon structure. The influence of temperature and duration on yield, moisture, and ash content was analysed. Experimental results indicated that the optimal carbonisation temperature was 500°C, producing activated carbon with high adsorption capacity. Elemental and X-ray analyses confirmed the presence of calcite, microcline, and quartz minerals in the ash composition. The obtained adsorbents demonstrated favourable physicochemical and sorption properties, making them suitable for industrial wastewater purification and environmental protection applications. The research provides a cost-effective and eco-friendly approach to converting local agricultural and food waste into valuable adsorptive materials.
Keywords: Activated carbon; Walnut shell; Thermal pyrolysis